The Effect of Auditor Competency and Work Experience on Information Systems Audit Quality and Supply Chain (Case Study: Indonesian Bank) - Maya Sari, Nur Zeina; Susanto, Azhar (International Journal of Supply Chain Management, 2018)
Abstract- The purpose of this study is to determine the effect of auditor competence and work experience on the information systems Audit quality and supply chain in the Indonesian X Bank. This research has been done in the Indonesian X Bank. The number of samples in this study is 30. The data collected through questionnaires. The multiple linear analysis techniques that previously tested for validity, reliability test, and classical assumption test such as normality test used as analytical techniques. Data analysis using SPSS version 23 program .The results of the study prove that: 1. Work Experience has a positive effect on information systems audit quality and supply chain at the Indonesian X Bank. 2. Competence Auditor positively influences to information systems Audit quality and supply chain at the Indonesian X Bank.   Keywords: Work Experience, Auditor Competence, Information Systems Audit quality, Supply Chain, Indonesian Bank